Implementation of the Islamic Religious Education Learning Model for Deaf Students: Empirical Study in Salatiga State Special Middle Schools - Fischa Amila; Javad Ostadmohamadi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to find out 1). Implementation of learning models, methods and learning media for islamic religious education for deaf students at Salatiga State Special Middle Schools. 2). Difficulties and solutions made by teachers in implementing the learning model. Methodology: Research uses qualitative methods based on primary and secondary data sources. Data collection was obtained through observation, structured and unstructured interviews, and documentation. Meanwhile, the data analysis technique involves collecting, reducing, presenting, drawing conclusions, and checking the validity of the data which includes triangulation of data sources and triangulation of methods. Main Findings: The results of the research concluded that in the implementation (application) of the learning model, especially for deaf students, teachers used more sign language and movements, oral approaches, writing methods, training/practical activities, and the use of visual media. And not all learning models can be implemented perfectly in the teaching and learning process, especially for deaf students. Meanwhile, the methods used are lecture method, practice/exercise, drill, reflective maternal method, insist on writing, bang jo method, maching a card, provide captioning. and the learning media used are lcd, whiteboard, puzzle card, video, and traffic teaching aids. The difficulties faced by teachers in the learning process for deaf students are influenced by teacher and student factors. The expectations of Islamic Religious Education teachers in the future are to prioritize memorizing the practice of ablution and prayer (prioritizing the movements). Novelty/Originality of this study: The novelty of this research is that it examines the implementation of Islamic religious education learning for deaf students . As well as looking for solutions to the obstacles faced by teachers in teaching Islamic religious education to deaf students.